Enhanced silica ballasting from iron stress sustains carbon export in a frontal zone within the California Current. Issue 7 (3rd July 2015) - Brzezinski, Mark A.; Krause, Jeffrey W.; Bundy, Randelle M.; Barbeau, Katherine A.; Franks, Peter; Goericke, Ralf; Landry, Michael R.; Stukel, Michael R.
Abstract Nutrient dynamics, phytoplankton rate processes, and export were examined in a frontal region between an anticyclone and a pair of cyclones 120 km off the coast in the southern California Current System (sCCS). Low silicic acid: nitrate ratios (Si:N) and high nitrate to iron ratios (N:Fe) characteristic of Fe‐limiting conditions in the sCCS were associated with the northern cyclone and with the transition zone between the cyclones and the anticyclone. Phytoplankton growth in low‐Si:N, high‐N:Fe waters responded strongly to added Fe, confirming growth limitation by Fe of the diatom‐dominated phytoplankton community. Low Si:N waters had low biogenic silica content, intermediate productivity, but high export compared to intermediate Si:N waters indicating increased export efficiency under Fe stress. Biogenic silica and particulate organic carbon (POC) export were both high beneath low Si:N waters with biogenic silica export being especially enhanced. This suggests that relatively high POC export from low Si:N waters was supported by silica ballasting from Fe‐limited diatoms. Higher POC export efficiency in low Si:N waters may have been further enhanced by lower rates of organic carbon remineralization due to reduced grazing of more heavily armored diatoms growing under Fe stress. The results imply that Fe stress can enhance carbon export, despite lowering productivity, by driving higher export efficiency.